2023
DOI: 10.3390/su15064899
|View full text |Cite
|
Sign up to set email alerts
|

Survey Evaluation of Building Information Modelling (BIM) for Health and Safety in Building Construction Projects in Malaysia

Abstract: Traditional safety planning methods that rely on manual inspections result in labour-intensive, time-consuming, and inadequate information transmission, which has significant negative social and economic effects on our society, as well as financial and schedule losses for construction projects. Building information modelling (BIM) is useful for analysing workplace safety issues, preventing risks and hazards, and improving safety throughout the project’s life cycle. This study intends to pinpoint health and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Badrinath and Hsieh found that the key factors of project delivery success using BIM technology can drive the critical success factors of the project [21]. Alaloul et al emphasized the important role of BIM in risk identification, prediction, and mitigation during the construction process through the analysis of semistructured questionnaire data using SPSS 26 software, and they recognized that BIM can significantly improve construction project safety and reduce accident rates [22]. Therefore, it is essential to assess the performance of BIM applications in the construction industry.…”
Section: Literature Review 21 Performance Evaluation Of Bim Applicationmentioning
confidence: 99%
“…Badrinath and Hsieh found that the key factors of project delivery success using BIM technology can drive the critical success factors of the project [21]. Alaloul et al emphasized the important role of BIM in risk identification, prediction, and mitigation during the construction process through the analysis of semistructured questionnaire data using SPSS 26 software, and they recognized that BIM can significantly improve construction project safety and reduce accident rates [22]. Therefore, it is essential to assess the performance of BIM applications in the construction industry.…”
Section: Literature Review 21 Performance Evaluation Of Bim Applicationmentioning
confidence: 99%